Evaluation of Antioxidant Activity and In Silico Prediction of Bioactive Compounds from the n-Hexane Extract of Gracilaria compressa (C. Agardh) Greville - Syafrizayanti Syafrizayanti; Andre Priandoko; Mai Efdi (Indonesian Journal of Chemical Studies, 2026)
This study evaluated the antioxidant potential and in silico pharmacological properties of the n-hexane extract of Gracilaria compressa (C. Agardh) Greville. Antioxidant assays using DPPH and ABTS radicals demonstrated moderate to strong scavenging activities, with IC₅₀ values of 74.51 mg/L and 58.81 mg/L, respectively. LC–MS/MS profiling identified several major lipophilic compounds, including uvaretin, mangostanol, and palmitic acid. Molecular docking simulations against Cyclooxygenase-2 (COX-2) revealed that uvaretin exhibited the strongest binding affinity (–9.0 kcal/mol), supported by hydrogen bonding and hydrophobic interactions with key active-site residues. Pharmacokinetic evaluation based on Lipinski’s Rule of Five indicated favorable drug-likeness and bioavailability properties for the identified compounds. These findings suggest that G. compressa n-hexane extract contains bioactive constituents with promising antioxidant and anti-inflammatory potential for further pharmacological development of marine-derived compounds as candidate therapeutics agents, particularly in the design of natural COX-2 inhibitors, and supports their potential application in pharmaceutical and nutraceutical formulations.